Transforming agriculture with data-driven insights - Sarangi, Sanat; Pappula, Srinivasu (Indian Farming, 2019)
Agriculture forms a major fraction of the GDP of our country. Large parts of this ecosystem are yet untouched by technology that could significantly boost productivity while reducing cost. India is a country of small land-holders. Small farms often pose challenges in making affordable personalised assessment possible at different stages of cultivation from pre-sowing to post-harvest. Fortunately, in the last few years, several forces have helped shape the agriculture ecosystem to make a lot possible.